Efeito agudo dos diferentes protocolos de pré condicionamento isquêmico sobre a velocidade de atletas de natação em uma prova de 100 metros: estudo crossover - Vasconcelos, Wanessa Kelly Vieira de (2020)
Introduction: studies presented that ischemic preconditioning (IPC) is able to promote ergogenic effect on physical performance, however, there is no consensus on the protocols used and knowledge gaps on which one would present better results in speed tests in swimming. Objective: to analyze the acute effect of different PCI protocols on the physiological variables and the speed of swimming in a 100-meter race. Materials and Method: this is a randomized crossover clinical trial, in which 12 male athletes (16.2 ± 1.5 years), swimming practitioners for at least 3 years, were submitted to 4 protocols in a randomized way: 1) ischemic preconditioning in the upper limbs; 2) ischemic preconditioning in the lower limbs; 3) ischemic preconditioning in the upper and lower limbs; 4) control. The IPC session was performed bilaterally in the upper and lower limbs and in the supine position. It was used 80% of the pressure required to limit total blood flow, except for control protocol, where the cuff was positioned on the upper and lower limbs, and the restriction cycle consisted of inflating the cuff to 10% of the pressure needed to restrict total blood flow for 2 minutes, followed by 1 minute at 80% and a further 2 minutes at 10%, totaling 5 minutes, alternating with 5 minutes of reperfusion (0 mmHg). For all protocols, 4 restriction cycles of 5 minutes each, alternating with 5 minutes of reperfusion (0 mmHg), were performed in a total intervention of 40 minutes. The variables of heart rate, double product, blood lactate and the athletes' time in a 100-meter race in the crawl swim were analyzed. The data were formed in the computerized statistical package Statistical Package for the Social Sciences (SPSS - 21.0) and increased the mean and standard deviation, adopting a significance level of P ≤ 0.05. Results: there was no significant difference between the different protocols for the application of ischemic preconditioning on the athletes’ speed of swimming in a 100-meter event (P> 0.05). However, analyzing the absolute values of each swimmer, it is shown that the protocols of ischemic preconditioning in the upper and lower limbs were more effective in reducing the test time in 66% and 83% of the sample, respectively, when compared to the control protocol. Still, significant increases were found between the pre and post moments in the analyzed physiological variables, heart rate, double product (DP) and lactate (P <0.05), except for the DP in the PCI-CONT protocol (P> 0.05). Conclusion: There was no improvement in physical performance from a statistical point of view, however, individually, the protocols of ischemic preconditioning in the upper and lower limbs showed a reduction in the 100-meter run time in relation to the control group. Promising result, which may support the ergogenic effect of PCI in swimming athletes.